Dampak pemantauan sejawat terhadap biaya kafalah: pendekatan eksperimen - Agus Munandar (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2018)
This study aims to examines impact of peer monitoring on cost of kafalah financing. Based on mixed results on severals recents studies and the significance of this issue to islamic banking costing, it is important to recognize the condition under context to reduce cost kafalah financing. This study employes experimental method for confirming hypothesis. This study provides evidence that peer monitoring reduces cost of non-repayment in kafalah financing. This findings give implication for banks management when provides kafalah financing.